UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BUAH BELIMBING WULUH (Averrhoa bilimbi L.) ASAL KOTA WATAMPONE - St. Maryam; Saidah Juniasti; Rachmat Kosman (As-Syifaa Jurnal Farmasi, 2015)
It has been conducted the research on Assay of Antibacterial Activity of Ethanolic Extract of Wuluh Starfruit (Averrhoa bilimbi L.) The aim of this research is to determine the antibacterial activity. The initial screening assay conducted on several bacteria including Escheria coli, Pseudomonas aeruginosa, Salmonella typhi, Bacillus subtilis, Staphylococcus aureus, Streptococcus mutans, Vibrio cholerae, Shigella dysenteriae. Then, assay on the Minimum Inhibition Concentration (MIC) was carried out with some variations of concentration: 0,05%; 0,1%; 0,2%; 0,4%; 0,8%; and 1,6%. Test result of MIC was then followed by MKC test (Minimum Kill Concentration) using NA medium. The results showed that on concentration 0,4%; 0,8%; and 1,6% inhibit the growth of bacteria tested. Antibacterial activity of ethanolic extract of wuluh starfruit (Averrhoa bilimbi L.) was conducted by using the diffusion agat method. The result showed that the lowest concentration 0,4% ethanolic extract of wuluh starfruit (Averrhoa bilimbi L.) inhibit the growth of bacteria Shigella dysenteriae, Salmonella typhi, Pseudomonas aeruginosa, Vibrio cholerae, Escherichia coli and Staphylococcus aureus.